Effect of anti-tumor necrosis factor alpha therapy on bone health and biomarkers of bone turnover in Indian patients with ankylosing spondylitis - Shefali Khanna Sharma; Sandeep Mohanan; Surender K Sharma (Indian Journal of Rheumatology)
Background: We evaluated the relationship between bone mineral density (BMD) and biomarkers of bone turnover in ankylosing spondylitis (AS) patients treated with anti-tumor necrosis factor alpha (TNF-α) agents. Methods: Fifty-one AS patients were screened, of which 27 were started on anti-TNF therapy in accordance to the assessment of AS guidelines. Detailed assessments of erythrocyte sedimentation ratio (ESR), Bath AS disease activity index (BASDAI), Bath AS functional index (BASFI), Bath AS metrological index (BASMI), AS disease activity score-ESR, and AS quality of life (AsQOL) questionnaire were done at baseline and 6 months. Vitamin D, parathyroid hormone, and osteocalcin were measured along with BMD of the lumbar spine, anteroposterior (AP) and lateral view, and hip. Results: Out of 27 patients, 12 patients had osteoporosis. At 6 months, significant improvements were seen for BASDAI (mean 2.33 ± 1.08, P < 0.01), BASFI (3 ± 1.31, P < 0.01), BASMI (3 ± 3.05,P = 0.019), and AsQOL (4 ± 3.02, P < 0.01) and these correlated with a decrease in ESR (15.6 ± 10.8,P = 0.01) at 6 months. The mean increase in BMD at the neck of femur, total hip, and lumbar AP view was 3.2% (P = 0.007), 3.1% (P = 0.004), and 2.5% (P < 0.001), respectively. The serum alkaline phosphatase level increased from a mean value of 190.3 ± 70.8 IU/ml at baseline to 225.4 ± 59.8 IU/ml, which was statistically significant at the 6-month follow-up (P = 0.006). The serum osteocalcin levels showed an increasing trend from a mean value of 2.32 ± 1.6 ng/ml at baseline to 3.32 ± 3.02 ng/ml at 6 months. Conclusion: Anti-TNF-α has a beneficial effect on bone metabolism resulting in improved bone formation.